Self-awareness of domestic violence in the decision-making of divorced - Ashari, Anindya; Casmini, Casmini (Empathy : Jurnal Fakultas Psikologi, 2023)
It is difficult for domestic violence survivors to decide to divorce after experiencing psychological trauma, which decreases the level of their awareness. In this regard, the existential perspective of humanism views self-awareness as one of the factors that can encourage humans to take action to change their living conditions to be better than before. This study aims to explore the process of developing the self-awareness of domestic violence to be able to decide to divorce a husband who committed domestic violence using an existential-humanistic perspective. This study uses a qualitative method with a phenomenological approach and involves three female domestic violence as a research subject. Research data was collected through in-depth interviews by exploring the meaning of the experience of domestic violence survivors who had decided to divorce. The results showed that the divorce decisions taken by the domestic violence survivors were related to increasing self-awareness. Domestic violence survivors who reach a higher level of self-awareness are significantly more empowered and able to make better decisions in their lives.Keywords: Divorce decision making, domestic violence, self-awareness